Marfan syndrome: Evolving organ manifestations—A 10‐year follow‐up study. Issue 2 (11th December 2019) - Vanem, Thy Thy; Böker, Tordis; Sandvik, Gunhild F.; Kirkhus, Eva; Smith, Hans‐Jørgen; Andersen, Kai; Drolsum, Liv; Lundby, Rigmor; Røe, Cecilie; Krohg‐Sørensen, Kirsten; Geiran, Odd R.; Paus, Benedicte; et al.
Abstract: The age‐dependent penetrance of organ manifestations in Marfan syndrome (MFS) is not known. The aims of this follow‐up study were to explore how clinical features change over a 10‐year period in the same Norwegian MFS cohort. In 2003–2004, we investigated 105 adults for all manifestations in the 1996 Ghent nosology. Ten years later, we performed follow‐up investigations of the survivors ( n = 48) who consented. Forty‐six fulfilled the revised Ghent criteria. Median age: females 51 years, range 32–80 years; males 45 years, range 30–67 years. New aortic root dilatation was detected in patients up to 70 years. Ascending aortic pathology was diagnosed in 93 versus 72% at baseline. Sixty‐five percent had undergone aortic surgery compared to 39% at baseline. Pulmonary trunk mean diameter had increased significantly compared to baseline. From inclusion to follow‐up, two patients (three eyes) developed ectopia lentis, four developed dural ectasia, four developed scoliosis, three developed incisional or recurrent herniae, and 14 developed hindfoot deformity. No changes were found regarding protrusio acetabuli, spontaneous pneumothorax, or striae atrophicae. The study confirms that knowledge of incidence and progression of organ manifestations throughout life is important for diagnosis, treatment, and follow‐up of patients with verified or suspected MFS.